Staged percutaneous coronary intervention followed by minimally invasive mitral valve surgery versus combined coronary artery bypass graft and mitral valve surgery for two-vessel coronary artery disease and moderate to severe ischemic mitral regurgitation - Mihos, Christos G.; Xydas, Steve; Williams, Roy F.; Pineda, Andrés M.; Yucel, Evin; Davila, Hector; Beohar, Nirat; Santana, Orlando (Journal of Thoracic Disease; Vol 9, Supplement 7 (June 01, 2017): Journal of Thoracic Disease (Innovations in the management of valvular and structural heart disease), 2017)
Background: The optimal treatment for concomitant two-vessel coronary artery disease (CAD) and moderate to severe ischemic mitral regurgitation (IMR) remains unclear. We compared the results of a staged percutaneous coronary intervention followed by minimally invasive mitral valve surgery (PCI+MIVS) versus combined coronary artery bypass graft and mitral valve surgery (CABG+MVS) in this population. Methods: All consecutive patients with two-vessel CAD and moderate to severe IMR, who underwent PCI+MIVS or CABG+MVS at our institution between February 2009 and April 2014, were retrospectively evaluated. Results: There were nine patients identified who underwent PCI+MIVS, and 15 who underwent CABG+MVS, with a mean age of 71±7, and 70±7 years, respectively (P=0.86). The remaining baseline characteristics were similar between both groups, with the exception of a higher prevalence of pre-operative clopidogrel administration (78% versus 27%, P=0.03) and left anterior descending plus left circumflex CAD (78% versus 27%, P=0.03), in those who underwent PCI+MIVS. The PCI+MIVS approach was associated with decreased mean cardiopulmonary bypass (111±41 versus 167±49 min, P=0.01) and aortic cross-clamp (79±32 versus 129±35 min, P=0.003) times, and less median number of intraoperative packed red blood transfusions {2 [interquartile range (IQR), 0–2] versus 3 units (IQR, 1–4), P=0.05}, when compared with CABG+MVS. The rate of mitral valve repair, postoperative complications, 30-day mortality, and 1-year survival did not differ between the surgical approaches. Conclusions: PCI+MIVS for two-vessel CAD and moderate to severe IMR is feasible, and associated with satisfactory outcomes, as compared with CABG+MVS.